Factors promoting sustainability of NURHI programme activities in Ilorin and Kaduna, Nigeria: findings from a qualitative study among health facility staff. Issue 10 (29th October 2020) - Olumide, Adesola Oluwafunmilola; McGuire, Courtney; Calhoun, Lisa; Speizer, Ilene; Babawarun, Tolulope; Ojengbede, Oladosu
Abstract : Objectives: The Nigerian Urban Reproductive Health Initiative (NURHI) was implemented in six urban sites in Nigeria from 2009 to early 2015. Under a second phase (NURHI-2), activities ceased operations in four of the original six sites in 2015 (Ilorin, Abuja, Benin City and Zaria), and continued in two sites (Kaduna and Ibadan). This paper examines the sustainability of facility-based intervention activities implemented under NURHI-1 in Ilorin and Kaduna. Methods: A qualitative study that used in-depth interviews was conducted with 31 service providers purposively selected from 10 of the NURHI-1 intervention facilities in Ilorin and six in Kaduna. Interviews were digitally recorded and transcripts uploaded into ATLAS.ti for analysis. Structured observations to document renovations implemented during the NURHI-1 interventions were also conducted in the health facilities. Results: Family planning (FP) awareness creation within the facilities and integration of FP into existing maternal and child health and HIV services, were sustained in both cities. The majority of the equipment supplied as part of the NURHI 72-hour clinic makeover were still functional in both cities. Respondents in both cities reported that FP awareness and demand were sustained. On the whole, challenges with sustaining activities were reported more among respondents in Ilorin than Kaduna. In Ilorin, NURHI outreach activities and trainings, had discontinued while in Kaduna, they were no longer being implemented to the same degree as occurred during NURHI-1. Inadequate funds was a major reason for discontinued activities in both cities while integration of FP into existing services enhanced sustainability. Conclusions: Many activities were not sustained in Ilorin compared with Kaduna although FP awareness and demand remained high in both cities. Integration of FP into existing services promoted sustainability in Ilorin and Kaduna. A gradual closeout of donor projects with concomitant input from government and indigenous institutions could be useful in sustaining donor activities.